Carbon nanotube‐polybutadiene‐poly(ethylene oxide)‐based composite fibers: Role of cryogenic treatment on intrinsic properties. (4th September 2022) - Gürbüz, Remzi; Sarac, Baran; Soprunyuk, Viktor; Rezvan, Amir; Yüce, Eray; Schranz, Wilfried; Eckert, Jürgen; Ozcan, Ali; Sarac, A. Sezai
Abstract: The low‐temperature response and the notion of crystallization kinetics are critical for developing elastomeric composite fibers, thus the crystallization and mechanical properties are essential for the application of composites of polybutadiene at low temperatures. Despite the high amount of fiber joining and entanglement due to polymers' low glass transition, a defect‐free micro‐scale electrospun carbon nanotube (CNT)‐containing poly(ethylene oxide) (PEO) and polybutadiene (PBu) composite elastomeric fibers with uniform fiber diameter and distribution are successfully fabricated. Thermomechanical behavior analyzed via frequency‐dependent dynamic mechanical analysis under cryogenic conditions shows a remarkable increase in decomposition temperatures ( T end ) and storage and loss modulus at cryogenic temperatures, particularly when small amounts of CNTs are present. Dynamic mechanical treatment from 120 K to elevated temperatures yields a pronounced logarithmic increase in T end by an increase of PEO content (from BEC1 to BEC4) compared to the treatment from 300 K. Through X‐ray diffraction, large shifts toward larger 2θ and formation of new crystals are observed, particularly for the BEC4 sample with high PEO content. Nanoparticles after cryo‐treatment linked with crystallinity are registered by ultra‐high resolution scanning electron microscopy. Improving the thermal and mechanical properties is critical in developing high‐performance composite fibers for cryogenic engineering applications, especially for future research to facilitate them in aerospace and low‐temperature medical and surgical treatments.